A Moderate Zinc Deficiency Does Not Alter Lipid and Fatty Acid Composition in the Liver of Weanling Rats Fed Diets Rich in Cocoa Butter or Safflower Oil - Edgar Weigand; Jennifer Egenolf (Journal of Nutrition and Metabolism)
The aim of the study was to examine whether a moderate zinc deficiency alters hepatic lipid composition. Male weanling rats, assigned to five groups (8 animals each), were fed low-carbohydrate high-fat diets supplemented with 7 or 50 mg Zn/kg (LZ or HZ) and 22% cocoa butter (CB) or 22% safflower oil (SF) for four weeks. One group each had free access to the LZ-CB and LZ-SF diets, one group each was restrictedly fed the HZ-CB and HZ-SF diets in matching amounts, and one group had free access to the HZ-SF diet (ad libitum control). The rats fed the LZ diets had significantly lower energy intakes and final body weights than the ad libitum control group, and lower plasma and femur Zn concentrations than the animals consuming the HZ diets. Hepatic cholesterol, triacylglycerol and phospholipid concentrations, and fatty acid composition of hepatic triacylglycerols and phospholipids did not significantly differ between the LZ and their respective HZ groups, but were greatly affected by dietary fat source. In conclusion, the moderate Zn deficiency did not significantly alter liver lipid concentrations and fatty acid composition.